Editorial management of an open access journal in consolidation: an analysis of the Revista Latino-Americana em Avaliação do Ciclo de Vida (LALCA) - Appel, André Luiz; Alves, Larissa de Araújo; Braga, Tiago Emmanuel Nunes; Rodrigues, Thiago Oliveira (Ciência da Informação em Revista, 2020)
Scholarly journals in consolidation, in general, cannot rely on well-established sources for generating and monitoring indicators for performance analysis, since these journals are not yet indexed by traditional databases. Facing this problem, this study aimed at the analysis and experimentation of performance evaluation indicators, tools and methodologies for the Revista Latino-Americana em Avaliação do Ciclo de Vida, which is in a consolidation stage. From the list of authors of the articles already published by LALCA, complementary data were collected, such as geographic origin, academic titles, affiliation, among others, in addition to data related to the access and use statistics of the Journal and its articles, using as data sources the platforms Open Journal Systems, Lattes, and Open Researcher and Contributor ID and other profiles and/ or personal or professional pages, and Google Analytics. The treatment and analysis of generated data provided insights that can assist the journal’s editorial team on the management process and its consequent qualification and consolidation, as well as instigating the expansion and reinforcement of the importance recording and curation of useful metadata for journal managing along their consolidation